PENDAMPINGAN PRAKTEK KEAGAMAAN FARDHU KIFAYAH PADA WARGA BINAAN LEMBAGA PEMASYARAKATAN KELAS II B PANYABUNGAN - Kasman Kasman; Aulia Rahman (E-Amal: Jurnal Pengabdian Kepada Masyarakat, 2023)
Correctional Institutions are government institutions that carry out coaching programs for convicts based on the Correctional System. The Correctional System focuses on care, coaching, education and guidance for correctional inmates with the aim of restoring the basic unity of relationships between individual inmates and society. The education that prison inmates receive is not in the form of cruelty or slavery so that in the future they will not repeat their crimes, for example, but rather in the development of competence, talent and potential in every inmate. The existence of the Class II B Penitentiary in Panyabungan, Mandailing Natal district, is a place for fostering and developing competence, especially in terms of knowledge and religious practices of the inmates. The method that the author uses in this service is the Asset Based Community Development (ABCD) method. This method utilizes assets and potentials around the environment and is controlled by the local community. The mentoring technique that will be carried out in this service is strengthening competence, namely regarding the practice of fardhu kifayah. This activity is important to know and provide religious education for prisoners, especially fardhu kifayah religious practices